Socialization Of Prevention Of Sexual Harassment Through Toilet Training In The Village Of Jagoi - Zulfahita Zulfahita; Citra Utami; Fitri Fitri; Fajar Wulandari; Iip Istirahayu (STKIP Singkawang, 2019)
Sexual harassment is still a taboo subject. This causes many victims of sexual harassment who do not dare to report to others or to the authorities. The number of cases of sexual harassment that occurred, both in the neighborhood and at school, it is important to give a good understanding of sexual harassment and how to avoid it. In response to this, the community service team needs to provide counseling about violence that occurs to children, how to communicate well with children, how to learn language in children, and the importance of conveying reproductive health to children properly. So that this socialization activity has a major role to prevent and provide knowledge and understanding of toilet training, personal areas, and sexual violence so as to prevent sexual harassment. The method used is socialization and documentation, this socialization activity was carried out on Friday, 18 January 2019 and took place in the village of Jagoi Babang. A facilitator must be very careful in the process of socialization, given the very heterogeneous conditions of the community, both the level of education, character, acceptance and understanding of the community. Socialization that is carried out to prevent sexual abuse especially in the area of private organs (sensitive areas) of the body is an important thing that should have been introduced to children from an early age. This is the duty of parents to be able to convey this information in good language and easily understood by children, because of the rampant incidence of sexual abuse, especially in children, whether boys or girls.